2004
DOI: 10.1111/j.1365-2133.2004.06051.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of topical 5-aminolaevulinic acid delivery by erbium:YAG laser and microdermabrasion: a comparison with iontophoresis and electroporation

Abstract: This basic study has encouraged the further investigation of ALA permeation by laser or microdermabrasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 26 publications
(27 reference statements)
1
99
0
Order By: Relevance
“…Among others, these include iontophoresis, ultrasound, microneedle puncture, temperature elevation as well as removal of hyperkeratosis and stratum corneum with curettage, tape stripping, microdermabrasion and laser ablation [17,23]. Conventional Er:YAG laser ablation of stratum corneum and superficial epidermis enhanced PpIX accumulation in murine superficial skin layers and subcutaneous tumors as well as ALA penetration of in vivo porcine skin [19,20]. In addition, pre-treatment with conventional erbium:YAG laser improved the anesthetic efficacy of topically applied lidocaine [18,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, these include iontophoresis, ultrasound, microneedle puncture, temperature elevation as well as removal of hyperkeratosis and stratum corneum with curettage, tape stripping, microdermabrasion and laser ablation [17,23]. Conventional Er:YAG laser ablation of stratum corneum and superficial epidermis enhanced PpIX accumulation in murine superficial skin layers and subcutaneous tumors as well as ALA penetration of in vivo porcine skin [19,20]. In addition, pre-treatment with conventional erbium:YAG laser improved the anesthetic efficacy of topically applied lidocaine [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Erbium lasers in particular have been used for laser-assisted cutaneous drug delivery [18][19][20][21], but the potential for deep AFR-assisted drug delivery has not been studied. Whole skin in vitro is a well-accepted standard for measuring drug uptake by passive diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis was: if the main limiting factor is tumor depth of not more than 2 mm, we will reduce the tumor to a depth less than 2 mm with another laser method, then eradicating the remainder of the tumor (if any) with PDT. By reference to a study demonstrating greater ALA penetration after surface treatment with an Er:YAG laser, it is also expected that greater saturation of the pathological tissue can be achieved with aminolevulinate [6][7]. Er:YAG laser (same as CO2) is itself an effective tool for the ablation of nonmalign, pre-malign, and malign tumors [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature data, access of 5-aminolevulinic acid (ALA) to the cells can be augmented 2 times with the help of electric impulses (17), and the production of photofrin IX can be increased by almost 3 times in comparison with passive diffusion of ALA (18). In this study, the lifetime of the pores was measured, and it was found that lifetime of electropores varied within an interval of milliseconds depending on electroporation parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In that way, electroporation could help: a) to reduce accumulation duration of a photosensitizer, b) to minimize the effective dose of the photodrug, c) to reduce the phototoxic effect of photosensitized damage on the organism. Few recent studies performed in vitro and in vivo have shown that electroporation could increase the effectiveness of PDT (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%